Betriebe in der ökologischen Transformation - Christian Hohendanner; Markus Janser; Florian Lehmer (Institut für Arbeitsmarkt- und Berufsforschung (IAB), 2024)
Die Anstrengungen zur Begrenzung des Klimawandels und zur Förderung ökologischer Nachhaltigkeit haben weitreichende Auswirkungen auf Betriebe und deren Beschäftigte. So müssen die Unternehmen ihre Geschäftsmodelle und Prozesse anpassen, um den Anforderungen einer umwelt- und klimafreundlicheren Wirtschaft gerecht zu werden. Gleichzeitig sehen sich Betriebe zunehmenden Fachkräfteengpässen gegenüber. Besonders herausfordernd ist es für Unternehmen geworden, Beschäftigte mit den benötigten umwelt- bzw. klimafreundlichen Kompetenzen ("Green Skills") zu finden bzw. bestehendes Personal in diese Richtung weiterzubilden. Bisherige umwelt- bzw. klimaschädliche Kompetenzen ("Brown Skills") werden zunehmend ersetzt oder stehen unter erhöhtem Transformationsdruck. Neben der in der wissenschaftlichen Literatur verwendeten Differenzierung zwischen Green Skills und Brown Skills benutzen wir den ebenfalls international verwendeten Begriff der "White Skills". White Skills sind die verbleibenden Kompetenzen, die weder zur Verbesserung noch zur Verschlechterung von Klima und Umwelt beitragen bzw. nicht eindeutig als Green Skills oder Brown Skills klassifiziert werden konnten. [...] – – Efforts to mitigate climate change and promote environmental sustainability have far-reaching implications for businesses and their employees. These efforts require firms to adapt their business models and processes to meet the demands of a greener economy. At the same time, firms are facing an increasing shortage of skilled labour. It has become particularly challenging for companies to find employees with the necessary environmentally and climate-friendly skills. In order to trace the importance and development of green skills in companies in recent years, we aggregate the Greenness of Jobs Indicator (GOJI) generated at the occupational level to the establishment level. This allows us to analyse how the proportion of establishments and their employees with significant shares of green, brown and white skills has developed in recent years since 2012. The results show that establishments with green skills are tending to gain in importance in quantitative terms. The analysis suggests that establishments with green skills may be somewhat better positioned to compete for labour, although there is no evidence of climate quitting, i.e. employees leaving brown establishments in favour of green establishments. However, the data shows that women are more frequently represented in establishments with green skills than in those with brown skills. This could indicate that establishments with green skills are more attractive to women. Overall, the study shows that the ecological transformation brings both challenges and opportunities for companies. While labour shortages are a problem, companies with green skills may be better positioned to meet these challenges and benefit from the opportunities that arise.
Keywords: 330; Green Skills; brown Sklills; Klimawandel; Betriebe